Adaptation Futures 2025: CGIAR’s Africa‑Focused Contributions and Takeaways - Koren, Judith; Edward-Uwadiale, Regina (2025)
As climate change intensifies, its cascading impacts on food and water systems threaten livelihoods, ecosystems, and economic stability worldwide. Even at 1.5°C of warming, agricultural productivity and human well-being face irreversible losses, underscoring the urgent need to scale up adaptation. The Adaptation Futures 2025 conference in Ōtautahi Christchurch, New Zealand (13-16 October), brought together scientists, policymakers, and community leaders to advance solutions that are locally led, equitable, and grounded in evidence. A central message emerged: adaptation must scale and accelerate with local communities at the center of these efforts.